Prominent features in isotopic, chemical and dust stratigraphies from coastal East Antarctic ice sheet (Eastern Wilkes Land). (June 2017) - Caiazzo, L.; Baccolo, G.; Barbante, C.; Becagli, S.; Bertò, M.; Ciardini, V.; Crotti, I.; Delmonte, B.; Dreossi, G.; Frezzotti, M.; Gabrieli, J.; Giardi, F.; et al.
Abstract: In this work we present the isotopic, chemical and dust stratigraphies of two snow pits sampled in 2013/14 at GV7 (coastal East Antarctica: 70°41′ S - 158°51′ E, 1950 m a.s.l.). A large number of chemical species are measured aiming to study their potentiality as environmental changes markers. Seasonal cluster backward trajectories analysis was performed and compared with chemical marker stratigraphies. Sea spray aerosol is delivered to the sampling site together with snow precipitation especially in autumn-winter by air masses arising from Western Pacific Ocean sector. Dust show maximum concentration in spring when the air masses arising from Ross Sea sector mobilize mineral dust from ice-free areas of the Transantarctic mountains. The clear seasonal pattern of sulfur oxidized compounds allows the dating of the snow-pit and the calculation of the mean accumulation rate, which is 242 ± 71 mm w.e. for the period 2008–2013. Methanesulfonic acid and NO3 − do not show any concentration decreasing trend as depth increases, also considering a 12 m firn core record. Therefore these two compounds are not affected by post-depositional processes at this site and can be considered reliable markers for past environmental changes reconstruction. The rBC snow-pit record shows the highest values in summer 2012 likely related to large biomass burning even occurred in Australia in this summer. The undisturbed accumulation rate for this site is demonstrated by the agreement between the chemical stratigraphies and the annual accumulation rate of the two snow-pits analysed in Italian and Korean laboratories. Graphical abstract: Highlights: Ions, MSA, I, Br, BC and dust record from coastal East Antarctica are presented. Seasonal pattern of each markers is highlighted by comparison with δ 18 O. NssSO4 2− and δ 18 O are chosen for annual layer counting. The mean accumulation rate over the period 2008–2013 is 242 ± 71 mm w.e.. Nitrate and MSA appear to be well preserved in this high accumulation rate site.